Someone answer urgent and if so I will mark brainliest
![Someone answer urgent and if so I will mark brainliest class=](https://us-static.z-dn.net/files/de6/4dcedfdc4667065e295f454c99856140.png)
Answer:
B) (x,y) -> (-x,y)
Step-by-step explanation:
By reflecting across the y axis, all y values stay the same, therefore no matter what happens to the x, the second half will be y -> y
Because of the reflection across the y axis, you are simply taking all x values and multiplying by -1 to get x -> -x.
Thus, (x,y) -> (-x,y)